First Report of a Case of Ocular Infection Caused by Purpureocillium lilacinum in Poland - Robert Kuthan; Anna K. Kurowska; Justyna Izdebska; Jacek P. Szaflik; Anna Lutyńska; Ewa Swoboda-Kopeć (Pathogens, 2021)
This report describes the first case of an ocular infection induced by Purpureocillium lilacinum in Poland. The patient was a 51-year-old immunocompetent contact lens user who suffered from subacute keratitis and progressive granulomatous uveitis. He underwent penetrating keratoplasty for corneal perforation, followed by cataract surgery due to rapid uveitic cataract. A few weeks later, intraocular lens removal and pars plana vitrectomy were necessary due to endophthalmitis. The patient was treated with topical, systemic, and intravitreal voriconazole with improvement; however, the visual outcome was poor. The pathogen was identified by MALDI-TOF MS.